Trial by fire, water, and soot : Kansas State University's collection disaster plan dissected and what you can learn from our disaster - Turvey-Welch, Michelle R.; Talbot, Kathryn (My University, 2018)
How would your collection disaster plan fare in a large-scale disaster event? Do you have a plan? Are the major players aware of the plan and their role? In May 2018, Kansas State University's Hale Library experienced a fire which resulted in soot and water damage to all collections. Scale of damage varied widely by location in the building. Come to hear how our disaster plan worked, what we would do again, what we would change and refine moving forward, and how our plan was applied in a large-scale library collection disaster event.
Keywords: Libraries; Collection disasters; Emergency management; Library buildings; Preservation; Library buildings--Safety measures--Handbooks, manuals, etc.; Library materials--Conservation and restoration--Handbooks, manuals, etc.; Emergency management--Handbooks, manuals, etc.